Coping Strategies among Post Myocardial Infarction Patients with Anxiety Symptoms - R Bagherian Sararoudi,; M Maroofi,; M Fatolah Gol,; H Saneie (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2010)
BACKGROUND AND OBJECTIVE: Despite anxiety symptoms are common among post myocardial infarction patients the link between the coping methods and anxiety symptoms among these patients has not yet been cleared. The aim of this study was to compare coping methods among post-MI patients with and without anxiety symptoms.METHODS: One hundred consecutive patients following MI admitted to the CCU wards of the hospitals in Isfahan were selected. Data were collected by using Jalowiec coping, hospital anxiety and depression, and Norbeck social support scales. Regarding cut off point in hospital anxiety subscales the patients were divided into two groups with and without anxiety symptoms. FINDINGS: Forty two patients (42%) suffered from anxiety symptoms. Generally, significant difference was found between two groups with and without anxiety symptoms in coping styles (F= 10.213, p<0.0001). Also, the results indicated significant differences in coping styles including confrontive coping (F=24.771, p=0.0001), optimistic coping (F=21.937, p=0.0001), emotive coping (F=40.741, p=0.032), supportant coping (F=19.629, p=0.0001) and self-reliant coping (F=11.815, p=0.001).CONCLUSION: Considering the role of different factors on coping methods, study of the role of personality and cognitive variables on coping styles among post MI patients is purposed.